Food security in environmentally-oriented settlements:: a case study of PDS Virola Jatobá, Transamazônica, Pará State, Brazil - Santos Júnior, Cezário Ferreira dos; Sá, Tatiana Deane de Abreu; Porro, Noemi Sakiara Miyasaka; Porro, Roberto (Sustainability in Debate, 2017)
This work analyses the level of food security among family farmers settled in the "agrarian frontier" of the Brazilian Amazon region. The study was conducted in the settlement of PDS Virola Jatobá, in the municipality of Anapu (Pará State). In this modality of environmentally oriented settlements, family farmers devote the areas assigned to alternative use to agricultural activities. On the other hand, the areas identified as legal reserves are employed for extractivist and community forest management activities. A total of 32 interviews and 75 socioeconomic questionnaires were carried out at the family production unit level. Questions aimed at identifying the production, consumption and income values, as well as understanding ongoing productive transformations. Research results allowed the elaboration of a typology, based on the principal activity leading to income generation within the family production unit. The typology pointed out to changes, not only in the traditional production practices and as a consequence of environmental factors, but also in the agricultural production model itself, with different income generation strategies.